RANCANG BANGUN SISTEM INFORMASI AKADEMIK PADA SMA NEGERI 15 BATAM - Sophia, Puteri Zarith; Utnasari, Intan (Computer Science and Industrial Engineering, 2020)
Along with the rapid development of technology, the need for information is required in support the activities of an organization, especially information that is produced should contain the correct values, timely, accurate and of course save time. School sman 15 batam in this discussion is one of the agency/organization that is engaged in the field of education are still using the system information manually, the system is still there using a sheet of paper and the archive so it can cause data-data that is easily lost or damaged, the data-school data such as data of students, teachers, and the data value is sometimes hard to find when needed, this research aims to design information systems academic school web-based Method used to build this information system is using the waterfall method. The results of this study indicate that the use of the system web-based academic information can be accessed easily as well as provide information that is accurate and timely. This web application is expected to be applied and implemented in order to help the school sman 15 Batam in facilitating the process of teaching and learning